Structural and functional characterization of the brain-specific dynamin superfamily member RNF112 - Ya-Ting Zhong; Li-Li Huang; Kangning Li; Bingke Yang; Xueting Ye; Hao-Ran Zhong; Bing Yu; Menghan Ma; Yuerong Yuan; Yang Meng; Runfeng Pan; Haiqing Zhang; et al. (Proceedings of the National Academy of Sciences, 2025)
Most members of the dynamin superfamily of large guanosine triphophatases (GTPases) have an ability to remodel membranes in response to guanosine triphosphate (GTP) hydrolysis. Ring Finger Protein 112 (RNF112) (ZNF179/neurolastin) is a recently identified brain-specific dynamin-like protein possessing a really interesting new gene (RING) finger domain. Despite its essential role as an E3 ligase in neuron development, the architecture of RNF112 and the exact role of its GTPase activity remain unknown. Here, we determined the crystal structure of truncated RNF112 (RNF112 T ) containing a GTPase domain (GD) and three-helical middle domain (MD) at different nucleotide-loading states. In the nucleotide-free (apo) state, the monomeric RNF112 T remained in a unique self-restraint conformation characterized by docking of the proximal end of the MD to a groove in the GD. At the transition state of GTP hydrolysis, the MD was released from the GD and stretched aside to form an intertwined RNF112 T homodimer. Engineered RNF112 equipped with the C-terminal elements of ATL1 or the two transmembrane domains of yeast Sac1p relocated to the endoplasmic reticulum and was capable of mediating membrane remodeling. Taken together, our results offer necessary understandings of RNF112 as a dynamin-like large GTPase in its cellular function and provide insights into the functional mechanisms of dynamin superfamily proteins.